A study of French corporate diplomats in Brazil - Bilbault, Matthieu Raphael (2018)
As multinational companies gain in weight economically and socially in an ever-increasingly globalized world, relations with nation-states and actors from the civil society become more important in order to defend and promote business interests. Companies increasingly need to use corporate diplomacy to anticipate market shifts and minimize the risks that can potentially threaten their position. The purpose of this master thesis is to find out and understand more about French corporate diplomats and their methods to achieve their objectives in Brazil. Semi-structured interviews were conducted with French executives from big multinational companies, in order to look into their techniques and approach chosen with external stakeholders. This research follows an inductive methodology, aiming at pinpointing common themes among the participants and apply them to a larger target population. Findings first show that French management style and education system, explored in the literature review, deeply influences the way French corporate diplomats lead and implement their strategies in Brazil. Their rational-driven mind and hierarchical internal organization shape French corporate diplomacy in a pyramidal structure, in order to cope with regulatory abundance and put forward financial objectives. The homogeneity of their backgrounds also reinforces these similar techniques through a close corporate ecosystem where they can communicate on corporate diplomacy best practices. They tend to keep decision-making processes in small circles and view lobbying as a risky strategy in Brazil because of the political environment and history, even though they tie close links with Brazilian officials to voice their viewpoints.